Toll-like receptors in the induction of the innate immune response. - Aderem, A.; Ulevitch, R.J. (Nature, 2000)
The innate immune response is the first line of defence against infectious disease. The principal challenge for the host is to detect the pathogen and mount a rapid defensive response. A group of proteins that comprise the Toll or Toll-like family of receptors perform this role in vertebrate and invertebrate organisms. This reflects a remarkable conservation of function and it is therefore not surprising that studies of the mechanism by which they act has revealed new and important insights into host defence.